2012
DOI: 10.1007/s10552-012-9921-1
|View full text |Cite
|
Sign up to set email alerts
|

Poultry and livestock exposure and cancer risk among farmers in the agricultural health study

Abstract: Purpose The purpose of this study is to evaluate cancer risk associated with raising animals as commodities, which is associated with a variety of exposures, such as infectious agents and endotoxins. Methods Information was available for 49,884 male farmers in the Agricultural Health Study, who reported livestock and poultry production at enrollment (1993–1997). Cancer incidence data were obtained through annual linkage to state registries. Using Poisson regression analyses, we evaluated whether the number a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 33 publications
3
60
1
Order By: Relevance
“…Farmers experience low overall mortality but high rates of some cancers; this suggests that some or several agricultural exposures may be key determinants [5,6]. Indeed, positive associations between NHL and farm related exposures, including pesticides, fertilizers, chemicals, animals, viruses, and endotoxin, have been observed previously [3,5,7]. However, the wide variety of chemical and microbial exposures that occur simultaneously in agricultural production makes disentangling the effects of these factors challenging.…”
Section: Introductionmentioning
confidence: 94%
“…Farmers experience low overall mortality but high rates of some cancers; this suggests that some or several agricultural exposures may be key determinants [5,6]. Indeed, positive associations between NHL and farm related exposures, including pesticides, fertilizers, chemicals, animals, viruses, and endotoxin, have been observed previously [3,5,7]. However, the wide variety of chemical and microbial exposures that occur simultaneously in agricultural production makes disentangling the effects of these factors challenging.…”
Section: Introductionmentioning
confidence: 94%
“…This is consistent with a previous study by Beth-waite et al ., which found an increased risk for AML among workers employed in an abattoir [33], but not among butchers or meat packers who worked in retail or wholesale, nor among cattle, dairy or sheep farmers [33]. Furthermore, the Agricultural Health Study (AHS) did not find an elevated leukemia risk among farmers who worked with various types of livestock; however, findings specific for AML were not reported [41]. It should be noted that laboratory studies have found little evidence that animal viruses infect human cells [33,42].…”
Section: Discussionmentioning
confidence: 99%
“…The increased AML risk observed among women on farms, the 2-fold elevated risk among women in rural residences that were not farms, and the lack of association with crop acreage suggest that farm exposures other than crop pesticides may be important AML risk factors. For example, links between animal husbandry and increased leukemia risk have been reported in the AHS (Beane Freeman et al, 2012) and by others (Svec et al, 2005), though AML was not specifically examined. The etiologic pathway for animal exposures in the development of these cancers has not been clearly elucidated, but is hypothesized to involve infectious agents (Svec et al, 2005).…”
Section: Discussionmentioning
confidence: 99%